Smart City Concept for Integrated Citizen Information Smart Card or ICISC in DKI Jakarta - Muhammad Syarif Hartawan; Arman Syah Putra; Ayub Muktiono (Publisher Cv. Inara, 2020)
Abstract. The development of cities that adopt smart is very much around the world, many cities in the world have developed the concept of a smart city in all aspects of life from identity to law enforcement systems in the traffic sector, smart cities have begun to be implemented in the city of Jakarta from 2000 onwards, Starting from the online payment system to the use of CCTV in law enforcement in the city of Jakarta, almost all aspects of government have used the system, from absences to public service applications, in this study using the literature review method, by studying many previous studies in order to deepen research that is is being carried out and finding renewable research problems, this research will produce a proposed system that can be used in the future as a concept for the development of a smart city Jakarta, with the proposed system as renewable research from existing research.